Identification of a Compound That Inhibits the Growth of Gram-Negative Bacteria by Blocking BamA–BamD Interaction - Li, Yan; Zhu, Xiaohong; Zhang, Jing; Lin, Yuan; You, Xuefu; Chen, Minghua; Wang, Yanchang; Zhu, Ningyu; Si, Shuyi (Frontiers in Microbiology, 2020)
The demand for novel antibiotics is imperative for drug-resistant Gram-negative bacteria which causes diverse intractable infection disease in clinic. Here, a comprehensive screening was implemented to identify potential agents that disrupt the assembly of β-barrel outer-membrane proteins (OMPs) in the outer-membrane (OM) of Gram-negative bacteria. The assembly of OMPs requires ubiquitous β-barrel–assembly machinery (BAM). Among the five protein subunits in BAM, the interaction between BamA and BamD is essential for the function of this complex. We first established a yeast two-hybrid system to confirm the interaction between BamA and BamD, and then screened agents that specifically disrupt this interaction. From this screen, we identified a compound IMB-H4 that specially blocks BamA-BamD interaction and selectively inhibits the growth of E. coli and other Gram-negative bacteria. Moreover, our results suggest that IMB-H4 disrupts BamA-BamD interaction by binding to BamA. Strikingly, E. coli cells having been treated with IMB-H4 showed impaired OM integrity and decreased the abundance of OMPs. Therefore, an antibacterial agent was identified successfully using yeast two-hybrid system, and this compound likely blocks the assembly of OMPs by targeting BamA-BamD interaction in Gram-negative bacteria.identified an antibacterial agent that likely blocks OMPs assembly by targeting BamA-BamD interaction in Gram-negative bacteria.